2016
DOI: 10.1002/ana.24751
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy prevents the onset of Parkinson disease in patients with diabetes

Abstract: Objective: We studied the association between the statin dosage and the risk of Parkinson disease (PD) in diabetic patients in Taiwan. Methods: One million patients were randomly sampled from a National Health Insurance (NHI) database and followed from 2001 to 2008. Diabetic patients were screened by diagnosis of International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes, and statin dosage was determined according to the NHI pharmacy database. PD was diagnosed on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 31 publications
5
48
8
Order By: Relevance
“…Of the included studies, 6were from North America [14, 18-20, 22, 26] 4 were from Europe [8, 9, 17, 24], and 3 were from Asia [21, 23, 25]. The year of publication ranged from 2007 to 2016, thus spanning 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies, 6were from North America [14, 18-20, 22, 26] 4 were from Europe [8, 9, 17, 24], and 3 were from Asia [21, 23, 25]. The year of publication ranged from 2007 to 2016, thus spanning 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…However, only 5 observational studies mentioned about individual statin use such as simvastatin and atorvastatin and other statin [8, 18, 23, 24, 26]. A total of 4,877,059 study subjects were included in our quantitative synthesis of which 1,269,095 and 1,243,616 were men and women respectively; the discrepancy in these numbers is due to 2 studies, which did not contain information on gender [17, 18].…”
Section: Resultsmentioning
confidence: 99%
“…Greater than 50% of subjects participating in clinical trials of Alzheimer's disease are positive for ApoE4 [17]. Similarly, two meta-analyses have reported a correlation between statin therapy and a reduced risk in the development of Parkinson's disease [18,19]. Rosuvastatin, a widely prescribed HMG-CoA reductase inhibitor, has been used for the treatment of dyslipidemia (LDL-C) and has been proven to be more effective in comparison to other members of its class [20].…”
Section: Introductionmentioning
confidence: 99%
“…Lin and colleagues recently reported that among Taiwanese diabetic patients, statin use was associated with reduced risk of Parkinson disease (PD) . In their study, patients were randomly sampled from a National Health Insurance (NHI) database with follow‐up time from 2001 to 2008.…”
mentioning
confidence: 99%